Adaptive Business Analysis Methodologies; Enabling Agile Transformation in Complex Enterprises - Pourzeinali, Ashkan; Sonreet Kaur; Samer Kobrossy (Indonesian Journal of Science, Technology and Humanities, 2025)
Organizations must create flexible capabilities that enable agile transformations while keeping their strategic vision intact to succeed in today's rapidly changing markets. Traditional business analysis methodologies which rely on structured processes and comprehensive documentation face integration challenges with agile frameworks because they follow a rigid linear path. The research investigates how Adaptive Business Analysis Methodologies can effectively connect traditional business analysis processes with agile principles to help organizations operate effectively in complex and unpredictable settings. The study examines how adaptive business analysis encourages cross-functional teamwork along with iterative requirement collection and immediate decision-making in agile environments. The paper identifies key adaptive BA components such as stakeholder engagement and incremental delivery through an extensive analysis of industry case studies and academic literature alongside predictive analytics and value-driven governance. The study demonstrates organizations implementing adaptive BA methods achieve better project execution outcomes and stakeholder harmony along with faster innovation advances in software development and cloud computing domains. The research demonstrates that Adaptive Business Analysis Methodologies offers a solid structure to reach enterprise agility which becomes essential for businesses that transform digitally.